Pneumothorax as first presentation of ‘ABPA sans asthma’ - Preeyati Chopra; Rhea S. Suares; Rishabh Deshwal; Kranti Garg (Lung India)
In patients with severe asthma with allergic bronchopulmonary aspergillosis (ABPA), a variety of radiological manifestations are seen. Pleural involvement is rare, and a very few case reports of secondary spontaneous pneumothorax have been reported in the literature. Here, we report an even rarer case of secondary spontaneous pneumothorax in a patient of ABPA ‘without asthma’.